2023
DOI: 10.1038/s43018-023-00628-6
|View full text |Cite
|
Sign up to set email alerts
|

Persister cell phenotypes contribute to poor patient outcomes after neoadjuvant chemotherapy in PDAC

Xu Zhou,
Jingyu An,
Roma Kurilov
et al.

Abstract: Neoadjuvant chemotherapy can improve the survival of individuals with borderline and unresectable pancreatic ductal adenocarcinoma; however, heterogeneous responses to chemotherapy remain a significant clinical challenge. Here, we performed RNA sequencing (n = 97) and multiplexed immunofluorescence (n = 122) on chemo-naive and postchemotherapy (post-CTX) resected patient samples (chemoradiotherapy excluded) to define the impact of neoadjuvant chemotherapy. Transcriptome analysis combined with high-resolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In contrast with these findings, a RNA-Seq profiling study encompassed enriched ECM organization and collagen formation in NCT as compared to treatment-naïve PDAC. 38 A second gene expression study reported increased collagen transcription in NCRT-treated samples as compared to biopsies taken before the intended neoadjuvant therapy. 39 Taken together, this is an area of ongoing research, especially since a fibrotic ECM rich in collagens is a hallmark of PDAC, promoting tumor progression and chemoresistance.…”
Section: Nct Yields Enrichment Of Ribosomal and Metabolic Proteins As...mentioning
confidence: 99%
“…In contrast with these findings, a RNA-Seq profiling study encompassed enriched ECM organization and collagen formation in NCT as compared to treatment-naïve PDAC. 38 A second gene expression study reported increased collagen transcription in NCRT-treated samples as compared to biopsies taken before the intended neoadjuvant therapy. 39 Taken together, this is an area of ongoing research, especially since a fibrotic ECM rich in collagens is a hallmark of PDAC, promoting tumor progression and chemoresistance.…”
Section: Nct Yields Enrichment Of Ribosomal and Metabolic Proteins As...mentioning
confidence: 99%
“…This reversibility is a defining trait of tumor dormancy, underscoring its dynamic nature and the potential for dormant cells to re-enter active proliferation [ 25 ]. Drug-resistant persistent cells share some characteristics with dormant tumor cells in terms of reversibility; however, they differ in that removal from the drug environment promptly ends their dormancy, restoring sensitivity to the drug [ 34 ].…”
Section: What Is Tumor Dormancy?mentioning
confidence: 99%
“…Reversibility is also one of the important characteristics of the DTP state [18]. When a drug is discontinued, the tumor cells will regain sensitivity to the drug [19]. In other words, unlike the clonal evolution driven by gene mutations, the clonal complexity of recurrent tumors does not disappear during chemotherapy.…”
Section: Reversibilitymentioning
confidence: 99%